4CPS-058 Avoid simultaneus prescription between linezolid and voriconazole: pharmacokinetic study. (March 2019) - Idoate, AI; Leache, L; Aldaz, A
Abstract : Background: Taking linezolid (LIN) and voriconazole (VCZ) at the same time is common in routine clinical practice. Voriconazole is eliminated by hepatic metabolism mainly by CYP2C19 isoform and less by CYP3A4 and CYP2C9. Linezolid is 65% metabolised in two metabolites and the main metabolite is independent of cytochrome P450-isoenzymes. Purpose: The aim of the study was to analyse the potential interaction between LIN and VCZ in patients diagnosed with fungal and active bacterial infection who require both antiinfective drugs simultaneously. Material and methods: Single-centre retrospective observational study was carried out in patients under simultaneous treatment with LIN and VCZ between March 2009 and December 2015. VCZ serum baseline concentrations before treatment with LIN and after at least 3 days of combined therapy were analysed by liquid chromatography (HPLC). Oral VCZ clearance (CL/F in L/h) was estimated before (CL/Fb) and during treatment with LIN (CL/Fd LIN). It was assumed as VCZ therapeutic range 1.5–4.5 mcg/mL in Candida spp. infections and 2–4.5 mcg/mL in Aspergillus spp. Demographic variables (age, sex), treatment (dosing schedule, date and time of each administration), clinics (diagnosis, microbiological information, etc.) and kinetics (date and time of each sample extraction) were collected. Results: Five patients were analysed with a median age of 67 years (range: 57–73), all of them males. Mean daily dose ±SD administered were 454.5±157.2 mg (VCZ) and 1, 200 mg (LIN). Serum baseline concentration of VCZ before LIN was 2.7±0.8 mcg/mL. CL/Fb and CL/Fd of VCZ were, respectively, 6.3±1.7 L/h and 22.09±11.74 L/h, which represents a large increase of 250%. VCZ and LIN interaction generated infra-therapeutic VCZ concentrations in 80% of patients (n=4). Three patients had to change anti-infective treatment and two patients required increased VCZ dose up to 75% to reach at least the lower limit of the therapeutic range. Conclusion: Adding LIN to VCZ treatment increases VCZ clearance between 250%–700% and serum antifungal concentrations decrease clinically. This translates into a loss of effectiveness in antifungal treatment in 80% of cases. Therefore, the use of this combination is contraindicated and if clinically there is no other alternative, VCZ pharmacokinetic monitoring is recommended to ensure the effectiveness of antifungal treatment. References and/or acknowledgements: http://www.hanstenandhorn.com/news.htm No conflict of interest.